The Effect of Increasing Weight During Pregnancy on Newborn Baby Weight at Khodijah Daulay Clinic - Batubara, Siti Khadijah; Siregar, Lina Roito (PT Inovasi Pratama Internasional, 2022)
Factors that can affect the birth weight of a baby include internal environmental factors, external environmental factors, and factors related to the use of health facilities related to the frequency of pregnancy check-ups or antenatal care. This study aims to identify the effect of increasing body weight during pregnancy on the birth weight of the baby. The research design used in this research is descriptive correlation. The instrument in this study was secondary data obtained from data at the Khodijah Daulay Clinic, KMS for pregnant women, delivery records, and birth weight of the baby. The results showed that the average weight gain of the respondents during pregnancy was 10.74 Kg with a standard deviation of 1.358 and the lowest weight gain was 10 while the highest weight was 16 Kg. From the results of statistical tests with Product Moment Correlation, it was obtained that p value = 0.000 had a significant effect between increasing body weight during pregnancy and newborn weight. And also obtained a value ( r = 0.733 ) this means that the influence is quite strong with a positive direction, meaning that the more the mother's weight increases during pregnancy, the more the baby's weight increases.